Municipal COVID-19 Epidemiological Response: Level of Satisfaction among Households in Esperanza, Sultan Kudarat - E. Lasanas; C. Garcia; J. Tabago; A.P. Matampay (Universitas Pendidikan Indonesia (UPI), 2021)
This study was carried out to statistically quantify the level of satisfaction among residents in Esperanza, Sultan Kudarat, and the level of effectivity of the municipal COVID- 19 epidemiological response team on COVID- 19 response. In the Philippines, from the initial studies and information about the nature and behavior of the virus, the government settles on a plan of action around what mitigation strategies and control measures to implement. This present study was conducted to find out the level of satisfaction among the 30 selected respondents from seven reachable rural barangay in Esperanza, the Philippines in terms of food support, public health and safety protocols, as well as news and updates dissemination. Based on the result of the study, the level of effectiveness in terms of food support, implementation of public health and safety protocols, as well as news and updates dissemination is described as satisfied. It implies that the municipal COVID-19 epidemiological response team is effective. The result of this study will create a huge impact in the field of COVID-19 response in the Philippines, making the government aware of their plans such as mitigation strategies and control measures implemented, knowing the sentiments of the Filipino citizen amid a pandemic.